SURVEY OF ISLAMIC RELIGIOUS EDUCATION (PAI) TEACHER PROFESSIONALISM ON STUDENT LEARNING MOTIVATION IN ISLAMIC RELIGION SUBJECTS AT SD NEGERI 01 PEMATANG JERING VILLAGE SEI SUKA DISTRICT BATU BARA REGENCY - Muliatno; Indah Mawaddah (RADJA PUBLIKA, 2022)
This study uses a quantitative approach, where the symptoms are measured using numbers. The results of the research in this thesis, the professionalism of PAI teachers in SD Negeri 01 Pematang Jering Village, Sei Suka District, Batubara Regency are generally sufficient. Meanwhile, the motivation to learn is generally good. A teacher is said to be a professional if he is able to create a quality teaching and learning process and bring learning success as measured by the passing competencies achieved by students. Likewise, students are said to have ideal graduate competencies if they have mastered the subject matter well and are able to actualize it. The presence of a professional teacher will certainly have a positive impact on student development, both in knowledge and learning motivation.